Implementing Geospatial Web Services: A Resource Webliography. - Cynthia Dietz (Issues in Science and Technology Librarianship)
This paper is designed as a research tool for information specialists and science technology librarians seeking to build and understand geospatial web services (GWS). GWS permit users to dynamically access, exchange, deliver, and process geospatial data and products on the World Wide Web, no matter the platform or protocol. They are compliant with Open Geospatial Consortium (OGC) standards to advance interoperability. The paper briefly describes select GWS, OGC interoperability demonstrations, and software tools and applications that are fully or partly OGC compliant. Courses, cookbooks, and tutorials helpful to those seeking to build their own GWS are described. The use of GWS in geoportals is discussed briefly, particularly in those servicing spatial data infrastructures and scientific communities. Finally, challenges pertaining to the interoperability of GWS are noted in select publications and presentations. [ABSTRACT FROM AUTHOR]